Step
*
1
2
1
1
1
2
of Lemma
Legendre-annihilates-rpolynomial
1. n : ℕ
2. f : [r(-1), r1] ⟶ℝ
3. ∃k:ℕn. ∃a:ℕk + 1 ⟶ ℝ. ∀x:{x:ℝ| (r(-1) ≤ x) ∧ (x ≤ r1)} . ((f x) = (Σi≤k. a_i * x^i))
4. x : {x:ℝ| (rmin(r(-1);r1) ≤ x) ∧ (x ≤ rmax(r(-1);r1))} 
5. y : {x:ℝ| (rmin(r(-1);r1) ≤ x) ∧ (x ≤ rmax(r(-1);r1))} 
6. x = y
7. rmin(r(-1);r1) = r(-1)
8. rmax(r(-1);r1) = r1
⊢ Legendre(n;x) = Legendre(n;y)
BY
{ (RWO "-3" 0 THEN Auto) }
Latex:
Latex:
1.  n  :  \mBbbN{}
2.  f  :  [r(-1),  r1]  {}\mrightarrow{}\mBbbR{}
3.  \mexists{}k:\mBbbN{}n.  \mexists{}a:\mBbbN{}k  +  1  {}\mrightarrow{}  \mBbbR{}.  \mforall{}x:\{x:\mBbbR{}|  (r(-1)  \mleq{}  x)  \mwedge{}  (x  \mleq{}  r1)\}  .  ((f  x)  =  (\mSigma{}i\mleq{}k.  a\_i  *  x\^{}i))
4.  x  :  \{x:\mBbbR{}|  (rmin(r(-1);r1)  \mleq{}  x)  \mwedge{}  (x  \mleq{}  rmax(r(-1);r1))\} 
5.  y  :  \{x:\mBbbR{}|  (rmin(r(-1);r1)  \mleq{}  x)  \mwedge{}  (x  \mleq{}  rmax(r(-1);r1))\} 
6.  x  =  y
7.  rmin(r(-1);r1)  =  r(-1)
8.  rmax(r(-1);r1)  =  r1
\mvdash{}  Legendre(n;x)  =  Legendre(n;y)
By
Latex:
(RWO  "-3"  0  THEN  Auto)
Home
Index